Liver injury, SARS‐COV‐2 infection and COVID‐19: What physicians should really know?. Issue 3 (3rd May 2021) - Licata, Anna; Minissale, Maria Giovanna; Distefano, Marco; Montalto, Giuseppe
Abstract: Background & Aims: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is responsible for coronavirus disease 2019 (COVID‐19), which in males, especially in advanced age, can sometimes evolve into acute respiratory distress syndrome. In addition, mild to moderate alterations in liver function tests (LFTs) have been reported in the worst affected patients. Our review aims to analyse data on the incidence and prognostic value of LFT alterations, the underlying mechanisms and the management of pre‐existing liver disease in COVID‐19 affected patients. Methods: We searched available literature through online PubMed database using terms as "SARS‐CoV‐2, " "Liver damage, " "Liver Function tests, " "COVID‐19, " "pre‐existing liver disease, " "drug‐induced liver injury." Results: Available evidence suggest that there could be a relationship between SARS‐CoV‐2 infection and liver damage, although the underlying involved mechanism remains unclear. Cohort studies have shown that high ALT levels, low platelet counts and low albumin levels at admission and during hospitalisation are associated with a high mortality rate. Unfortunately, little is known about the impact of COVID‐19 on pre‐existing liver damage. While chronic viral infections or NAFLD are associated with an increased risk of COVID‐19 progression, patients with cirrhosis may have increased susceptibility to SARS‐CoV‐2 infection due to their systemic immunocompromised status. DILI seems common among hospitalised patient with severe pneumonia. Conclusion: Mild to moderate liver impairment during Covid‐19 is common, especially in patients with pre‐existing liver disease. Further studies should be performed in order to understand how pre‐existing liver conditions may influence and worsen progression of liver disease in COVID‐19 patients.